Acute effects of muscle mechanical properties after 2000-m rowing in young male rowers - Chang, C.-H.; Ho, C.-S.; Li, F.; Chen, C. -Y.; Yeh, H.-C.; Ho, C.-A. (PeerJ, 2024)
Background The mechanical properties of muscles, such as changes in muscle tone and stiffness, are related to sports performance and injuries. Rowers are at increased risk of muscle fatigue and injury during high-repetition and heavy-load cyclic muscle actions. In view of this, the aim of the present study was to investigate the acute effect on muscle tone and stiffness, as well as bilateral muscle asymmetry, in high school rowers after a 2000-meter rowing ergometer test.